2020
DOI: 10.1021/acs.macromol.0c01405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Isomer Design on Physicochemical Properties and Performance in High-Efficiency All-Polymer Solar Cells

Abstract: Combining the acceptor–donor–acceptor-type fused ring-based molecular architecture into a polymeric backbone is a promising strategy to design polymer acceptors for high-performance all-polymer solar cells (all-PSCs), and use of single isomer monomers is critical to control their physicochemical and photovoltaic properties. Here, two polymer acceptors (namely, PBI-α and PBI-β) based on two different building blocks are designed and synthesized for investigating the effect of regioisomerism of the building bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Thus, new D-A type polymer acceptors (PSMA) have been developed by polymerizing NFSMAs and other donating building blocks. [39][40][41]117,[166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181] Because different regio-isomers are found in the chemical structures of NFSMA molecules, controlling the RR of the PSMA is an emerging factor for their design and application in high-efficiency all-PSCs. In this section, we will review a library of examples of RR control in the photovoltaic polymers and summarize the impacts of directional, positional, and sequential RRs on the PSC performance.…”
Section: Effects Of Rr On Polymer Solar Cells (Pscs)mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, new D-A type polymer acceptors (PSMA) have been developed by polymerizing NFSMAs and other donating building blocks. [39][40][41]117,[166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181] Because different regio-isomers are found in the chemical structures of NFSMA molecules, controlling the RR of the PSMA is an emerging factor for their design and application in high-efficiency all-PSCs. In this section, we will review a library of examples of RR control in the photovoltaic polymers and summarize the impacts of directional, positional, and sequential RRs on the PSC performance.…”
Section: Effects Of Rr On Polymer Solar Cells (Pscs)mentioning
confidence: 99%
“…The lower PCEs are due, in part, to the inhomogeneous molecular structures with low positional RR of PSMAs. 40,41,167,169,170,187 To address these issues, He and co-workers recently demonstrated the importance of controlling the positional RR of the PSMAs. They rst obtained isomerically pure monomers through recrystallization and employed them to achieve rre PBTIC-g-2F2T PSMAs by polymerization (Fig.…”
Section: Rr Of Homopolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of polymer NFAs, the most reliable method of producing high performing polymeric NFAs is to take a calamitic NFA and copolymerize it with a short spacer. [65][66][67][68][69] At least one report has shown that the use of an electron-deficient spacer is beneficial. 70 Although this is a new field of study, it appears that the features that make calamitic NFAs successful are also applicable to polymeric NFAs.…”
Section: R a F Tmentioning
confidence: 99%
“…[13][14][15][16][17] Bromination on IC has attracted increasing attention over other halogenations (F, Cl, and I) on developing novel SMAs because of the emerging strategy of polymerizing SMAs towards highly efficient polymeric acceptors. [18][19][20][21] Interestingly, the SMAs with IC-Br were found to offer a superior performance over the ones with a dibrominated IC (IC-2Br). 22,23 The asymmetric existence of a single malononitrile group on IC leads to a positional isomerization of monobromination when synthesizing IC-Br from the corresponding monobrominated indanedione and malononitrile.…”
Section: Introductionmentioning
confidence: 99%